A Multicolor Fluorescence in situ Hybridization Approach Using an Extended Set of Fluorophores to Visualize Microorganisms - Lukumbuzya, Michael; Schmid, Markus; Pjevac, Petra; Daims, Holger (Frontiers in Microbiology, 2019)
Fluorescence in situ hybridization (FISH) with rRNA-targeted oligonucleotide probes is a key method for the detection of (uncultured) microorganisms in environmental and medical samples. A major limitation of standard FISH protocols, however, is the small number of phylogenetically distinct target organisms that can be detected simultaneously. In this study, we introduce a multicolor FISH approach that uses eight fluorophores with distinct spectral properties, which can unambiguously be distinguished by confocal laser scanning microscopy combined with white light laser technology. Hybridization of rRNA-targeted DNA oligonucleotide probes, which were mono-labeled with these fluorophores, to E. coli cultures confirmed that the fluorophores did not affect probe melting behavior. Application of the new multicolor FISH method enabled the differentiation of seven (potentially up to eight) phylogenetically distinct microbial populations in an artificial community of mixed pure cultures (five bacteria, one archaeon, and one yeast strain) and in activated sludge from a full-scale wastewater treatment plant. In contrast to previously published multicolor FISH approaches, this method does not rely on combinatorial labeling of the same microorganisms with different fluorophores, which is prone to biases. Furthermore, images acquired by this method do not require elaborate post processing prior to analysis. We also demonstrate that the newly developed multicolor FISH method is compatible with an improved cell fixation protocol for FISH targeting Gram-negative bacterial populations. This fixation approach uses agarose embedding during formaldehyde fixation to better preserve the three-dimensional structure of spatially complex samples such as biofilms and activated sludge flocs. The new multicolor FISH approach should be highly suitable for studying structural and functional aspects of microbial communities in virtually all types of samples that can be analyzed by conventional FISH methods.